2019
DOI: 10.5812/jhealthscope.83968
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Criteria Affecting Appropriate Allocation of Health System Resources to Different Diseases in Iran: A Qualitative Inquiry

Abstract: Background: Health policymakers need to use prioritization for resource allocation in the health system because of limitations to financial resources. Objectives: This study aimed to explore the criteria affecting the appropriate allocation of health system resources to different diseases. Methods: A qualitative study was carried out in 2017 using semi-structured interviews. Participants were chosen using purposeful and snowball sampling methods. Totally, 25 experts in the health care system were interviewed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Among the selected studies, eighteen identified social values through the use of expert opinions (7;12;18;19;21–34). One study identified social values merely by analyzing policy documents and national evidence (12), while two studies involved a public survey to elicit social values (34;35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the selected studies, eighteen identified social values through the use of expert opinions (7;12;18;19;21–34). One study identified social values merely by analyzing policy documents and national evidence (12), while two studies involved a public survey to elicit social values (34;35).…”
Section: Resultsmentioning
confidence: 99%
“…A total of thirteen studies assigned weights to the criteria (19;22;24–27;2934), while eight studies described the criteria qualitatively (7;12;18;21;23;28;30). The discrete choice experiment (31;34), technique for order of preference by similarity to ideal solution (25;27), the analytic hierarchy process (26;33) confirmatory factor analysis (30), and decision making trial and evaluation laboratory (32) methods had been applied to quantify the criteria.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that physicians are generally better equipped to estimate a patient's imminence in risk of death, given a particular health condition, which may explain this discrepancy between both groups of healthcare practitioners. Having a low valorization of the patient's risk of death may raise concerns since there's some empirical evidence suggesting that Portuguese lay people (Pinho and Borges, 2015) as well as the general population in other countries (Dolan et al ., 2005; Krűtli et al ., 2016; Gu et al ., 2015; Pinho and Borges, 2018), health professionals (Lian, 2001; Arvidsson et al ., 2012; Krűtli et al, 2016; Pinho and Borges, 2021) and even experts in healthcare systems (Hadian et al ., 2019) feel the obligation to save, in the first place, those patients in emergency and life-threatening conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The adherence of healthcare professionals to the waiting list criterion contrasts with international findings, where general practitioners contested this criterion (Krűtli et al ., 2016) or classified it as insignificant (Hadian et al ., 2019). Moreover, this finding does not support ethicists' normative claims that waiting time (first come, first served principle) is not morally justifiable (Persad et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation